Social Media's Democratic Footprint: A Review of Political Participation Trends - Nusantara, Garda; Kinkin Yuliaty Subarsa (Journal of Communication and Public Relations, 2025)
This literature review examines social media's role in increasing public political engagement in the digital era, synthesizing 17 scientific sources from the last five years. Digital transformation has reshaped political participation, fostering faster, more open, and decentralized interactions. The study explores five key themes: the theoretical basis of political participation, mechanisms for increasing engagement through social media (e.g., shaping public opinion via digital platforms and phenomena like "Emergency Warning"), digital mobilization strategies of political figures (illustrated by the "Anies Bubble" discourse and its use of symbols and narratives), the impact of information technology on political communication and elite-public interaction, and the challenges and opportunities of digital democracy, including disinformation, polarization, and digital literacy gaps. Findings indicate social media's strategic role in promoting broader political participation. However, realizing its full potential necessitates robust digital literacy, adaptive regulations, and responsible platform governance to enhance the quality of digital democracy.